MUSEUMSRUM - Raahauge, Kirsten Marie (Tidsskriftet Antropologi, 1997)
Kirsten Marie Raahauge: Museum’s Space The article discusses the interaction of objects and museums. It claims that a thing gets other tasks when becoming a “member” of a museum collection than those it had originally. In this way the museum object is viewed as a representative of both its own story and a representative of the culture that creates museums. The museum is considered as a local phenomenon that deals with universal tasks. The article tries to analyze the museum and its exhibition activity by considering the self-knowledge of the museum itself, and it questions whether the museums in our time are adjusted to the principles that once established the museum as an institution.